Similarity in meal plan use among first-year roommates. (1st January 2020) - van Woerden, Irene; Schaefer, David R.; Hruschka, Daniel; Vega-Lopez, Sonia; Adams, Marc; Bruening, Meg
Abstract: Objective: To examine if first-year roommates made similar meal plan decisions. Methods: Residence information for 1186 first-year students (N = 593 roommate pairs) and 559 floormates was obtained for the 2015–2016 academic year. Linear generalized estimating equations (GEEs) were used to examine if the number of meals students used over the semester was higher if their roommate used their meal plan more frequently. A logistic GEE examined joint meal plan usage between students and roommates for each month of the semester. To determine if residence, rather than roommate, explained the results, a simulation was conducted by randomly assigning the floormates to a same-sex roommate. Results: The number of meals students used in spring was higher if the students' roommate had used more meals in spring, even after controlling for the number of meals students used in fall (Female: β = 0.07, 99% CI = 0.00, 0.13; Male: β = 0.10, 99% CI = 0.02, 0.18). Students were more likely to use a meal with their roommate if they were on the same meal plan (Female: OR = 1.61, 99% CI = 1.27, 2.04; Male: OR = 1.57, 99% CI = 1.09, 2.25), and less likely after the first month of being roommates (Female: OR = 0.57–0.25; Male: OR = 0.50–0.22; p < 0.001). The simulation analysis indicated these findings were not due to shared residence. Discussion: Students' meal plan choices were associated with their roommates' meal plan choices. Roommates' joint meal plan usage was highest at the start of the year. Strategic roommate pairings may result in students using their meal plan more. Further research should determine the extent of roommate influence on students' diet.